Care and Support of Children with Type 1 Diabetes at School: The Turkish Experience - Şükrü Hatun; Gül Yeşiltepe Mutlu; Tuğba Gökçe; Özkan Avcı; Nazan Yardım; Zehra Aycan; Feyza Darendeliler (Galenos Yayincilik, 2021)
Diabetes care at school has recently appeared on the agenda of international diabetes organizations, the basic principles of which have been newly determined. The aim of this review was to summarize the activities and output of the Diabetes at School Program - a program that has been delivered in Turkey for the last 10 years - and to focus on different aspects of Diabetes Care at School through a national model. Recently, a detailed set of national regulations, including the basic principles proposed by the International Society for Pediatric and Adolescent Diabetes and the experience in Turkey, was prepared and has come into force. The future agenda includes giving priority to socio-economically disadvantaged regions, provision of an Individual Treatment Plan at School for each child with diabetes and ensuring that each school has an action plan for the care of children with diabetes. We believe that if all countries have programs and structured national regulations similar to the Diabetes at School Program, this will enable significant progress in the level of care delivered to children with diabetes.